Los editorialistas árabes que leen la filosofía occidental y la promoción de un humanismo secularizado - Abdelrahim, Abdelrahim (Sens public, 2018)
This article talks about a new cultural and intellectual phenomenon witnessed lately in the Arab world. We call it here “new humanist Arab movement” in view of its resemblance with what happened in Europe during the Renaissance and what happened in the Islamic world during the Golden Age. We believe this movement can be divided into 3 branches: Secular, reformist and anti-religious.